2011
DOI: 10.1590/s0100-54052011000400005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phytoplasma infection on the activity of peroxidase, β-1,3 glucanase and chitinase in corn plants

Abstract: In the present work we studied the effect of inoculating corn plants with the maize bushy stunt phytoplasma on the activity of the enzymes peroxidase, -1,3 glucanase and chitinase. The experiments were ca rried ou t inside a greenhou se. Pla nts of a resistant a nd a susceptible corn hybrid were inoculated by using infective Dalbulus maidis leafhoppers 10 days after sowing. When symptoms started to appear, leaf samples were collected at different periods to quantify enzyme activity. The resu lts showed a n in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
3
0
2
Order By: Relevance
“…Class III chitinases display substantial lysozyme activity with a probable direct anti-bacterial action [ 13 ], and PAL activity results in the eventual production of a wide range of phenolic compounds, such as flavonoids, anthocyanins and lignins, all of which have anti-microbial activity [ 42 ]. A class III chitinase gene was up-regulated in maize leaves infected by MBS phytoplasma [ 15 ] and grapevine leaves infected by BN phytoplasma [ 11 ], and a PAL gene was up-regulated in grapevine leaves infected with Ca. P. solani [ 43 ] and tomato leaves infected Ca.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Class III chitinases display substantial lysozyme activity with a probable direct anti-bacterial action [ 13 ], and PAL activity results in the eventual production of a wide range of phenolic compounds, such as flavonoids, anthocyanins and lignins, all of which have anti-microbial activity [ 42 ]. A class III chitinase gene was up-regulated in maize leaves infected by MBS phytoplasma [ 15 ] and grapevine leaves infected by BN phytoplasma [ 11 ], and a PAL gene was up-regulated in grapevine leaves infected with Ca. P. solani [ 43 ] and tomato leaves infected Ca.…”
Section: Discussionmentioning
confidence: 99%
“…Up-regulation of phloem protein 2 (PP2) in the phloem of apple proliferation (AP)-infected apple was linked with leaf discoloration [ 12 ]. Alcohol dehydrogenase is involved in alcohol utilization under hypoxic conditions, which occur during phytoplasma infection [ 10 ], class III chitinase can digest cell walls of bacteria that would likely not directly affect phytoplasmas as they lack cell walls [ 13 , 14 , 15 ], PAL catalyzes the first step of the phenylpropanoid pathway to synthesize many antimicrobial defence compounds and increased PAL activity has been associated with increased phenolic compounds in the phloem [ 16 , 17 , 18 , 19 , 20 , 21 ], and phloem proteins ( PP ) 1 and 2 physically limit pathogen spread by plugging sieve pores in the phloem as well as synthesizing and modulating systemic signals, such as cytosolic Ca 2+ , contributing to innate immunity [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…5, p≤0.05). Similarly, Junqueira et al (2011) reported that phytoplasma infection in the maize plants resulted in a significant increase in POD and CAT enzymes. Catalase is also one of the essential enzymes capable of protecting biological systems against free radical attack (Ighodaro and Akinloye, 2018) and is the most effective enzyme, which reduces H2O2 into H2O and O2 (Mhamdi et al, 2010;Alam et al, 2014;Veronica et al, 2017).…”
Section: Effect Of Phytoplasma Infection On Enzyme Activities (Pod An...mentioning
confidence: 91%
“…Existe ampla literatura sobre os mecanismos de patogenicidade de fitoplasmas. A infecção por esses microrganismos afeta a homeostase de nutrientes (Van Bel and Musetti 2019; Raiesi and Golmohammadi 2020) e provoca mudanças bioquímicas na planta, como evidenciado para MBSP (Junqueira et al 2004(Junqueira et al , 2011. A regulação da expressão de genes associados à síntese de fitohormônios tem sido evidenciada (Dermastia 2019).…”
Section: Mecanismos De Patogenicidade Dos Molicutes E Alterações De Plantas Infectadasunclassified